Pembinaan model resiliensi remaja sekolah / Ibrahim Taib - Ibrahim, Taib (2011)
The purpose of the study was to construct an adolescent resiliency model. The determinants in the relationship of resilience to coping skills, acculturation and protective factors were also identified. A sample of 510 adolescent students from government-aided schools (premier, elite, religious) in east coast state in the Peninsular Malaysia participated in the study. The students were from low socio-economic background, living in challenging conditions deficient in modern facilities, and exposed to adversity and risks. In spite of that, these students have shown academic excellence. The main objectives of this study were: (1) to identify resiliency among students in government-aided schools, (ii) to determine the role of protective factors (religion, core convictions, and spirituality) as moderators between resiliency and coping skills as well as protection against stress and difficulty, (iii) to determine the relationship between resiliency and coping skills, acculturation, and protective factors. A model was constructed through Structure Equation Modeling (SEM) based on empirical data to show and clarify the relationships among the factors under study. The model was later tested to determine if there was a fit with the data. Data were collected using questionnaires through survey methodology. SPSS programme was used to analyze the data, AMOS for model construction, and SmartPLS to generate moderation. The findings of the study indicate that there was a positive and significant relationship between resiliency and coping skills as well as protective factors. On the other hand, there was a negative relationship between resiliency and acculturation. The resulting analysis of SEM indicates that the model has a fit with all the four sets of independent variables ( χ² = 110.671, N= 510, P < 0.05, GFI= 0.965, AGFI= 0.939, TLI= 0.943, CFI= 0.961, RMSEA= 0.054, CMIN/DF= 2.459). The findings of the study also indicate that the protective factors were moderating coping skills and resiliency. The model which was also tested on gender and school types and locations shows that these differences were not significant. The findings of this study suggest that an intervention programme can be incorporated in the teaching and learning activities based on coping skills and resiliency. The outcome of the study also indicates that there are some important issues to be considered such as protective factors based on religion, core beliefs and spirituality which could enhance resiliency amongst adolescent students. Finally, the results of this study suggest that there should be a revision of items in the Adolescent Resiliency Attitude Scale (ARAS), and focus should be directed on psychometric analysis and other scales in research on resiliency. The findings from this study benefit students, parents, schools, the Ministry of Education, and society at large with regards to the importance of focusing on development and revival of children who have been exposed physically and emotionally to adversity and stressful situations. Adolescent students who possess high resiliency and coping skills are able to become knowledgeable generation with conviction, sincerity, and self-confident. Consequently, the nation will be able to generate first class human capital who will be the driving forces and leaders of the future in various disciplines.